Preclinical safety profile of RC88-ADC：a novel mesothelin-targeted antibody conjugated with Monomethyl auristatin E. (2nd January 2023) - Jiang, Jing; Li, Shenjun; Tang, Naping; Wang, Ling; Xin, Wei; Li, Shoufeng
Abstract: Mesothelin (MSLN) is an attractive therapeutic target for antibody drug conjugates (ADC) because of significant differences in expression pattern between diseased and normal tissues. RC88-ADC is a novel ADC, targeting MSLN, and inhibits tumor growth significantly in mice xenograft models. We performed an 11-week repeated dose toxicity study of RC88-ADC via intravenous injection in Cynomolgus Monkeys with an 8-Week recovery period according to International Conference on Harmonization (ICH) S9 and S6(R1). RC88-ADC was administered to groups of 5 male and 5 female monkeys at dose levels of 2.5, 5, and 10 mg/kg/2 weeks, meanwhile vehicle, naked antibody, small molecule groups were set up as the control. 4 animals died in 10 mg/kg group of RC88-ADC. The clinical symptoms mainly included ocular toxicity, weight loss and food intake decrease in the middle and high dose groups of RC88-ADC. RC88-ADC caused dose-related reversible myelosuppression, manifested as hematologic toxicity, which was consistent with the small molecule toxicity profile of its coupling. The highest non-severely toxic dose of RC88-ADC was 5 mg/kg in monkeys after repeated dosing. Nonetheless, the integrated analysis showed that RC88-ADC demonstrated an acceptable safety profile and provided an improved treatment window. These results pave the way for further investigation of RC88-ADC in humans.